Destructive and non-destructive evaluation of wood properties in selected timbers of Kerala - Dhanya P (Department of Wood Science, College of Forestry, 2012)
A study entitled “Destructive and non-destructive evaluation of selected timbers of Kerala” was conducted in the College of Forestry, Kerala Agricultural University, Vellanikkara, Thrissur during the period 2010-2012. The objective of the study was to evaluate the physical and mechanical properties of wood in timber species such as: teak (Tectona grandis L.f.), mahogany (Swietenia macrophylla King), anjily (Artocarpus hirsutus Lamk.), jack (Artocarpus heterophyllus Lamk.), acacia (Acacia auriculiformis A. Cunn. ex Benth.), rubber (Hevea braziliensis (H.B.K.) M. A.) and pyinkado (Xylia dolabriformis Benth.) using destructive and non-destructive methods. The study also aimed at evaluating the suitability of non-destructive techniques (NDT) and semi-destructive techniques (SDT) as predictors of timber properties under field conditions. Pilodyn 6J ((FUJI TECK, Tokyo, Japan) and treesonic microsecond timer (Fakkopp, Hungary) were the two non destructive equipments used in this study. In the present study, logs of the above species were collected from forest depots and retail outlets in Thrissur. Penetration depth of each species was found out using pilodyn and dynamic modulus of elasticity (MOE) was found out using the treesonic timer. Discs were taken for analysing specific gravity and the logs were subjected to various mechanical tests. Significant variation in specific gravity, mechanical properties, stress wave velocity and penetration depth were noticed between species. Significant negative correlation (1 per cent level) was noticed between specific gravity and pilodyn penetration depth in each of the species. Also, penetration depth was negatively related to modulus of rupture, dynamic MOE, modulus of rupture (MOR), radial hardness and fibre stress at limit of proportionality. Significant positive correlation was noticed between dynamic modulus of elasticity and all the parameters obtained from static bending tests especially static modulus of elasticity and modulus of rupture. It was also noticed that dynamic MOE showed significant correlation (5 per cent level) with radial and tangential hardness. Significant positive correlation was found between stress wave velocity and all the parameters obtained from static bending test, and tensile strength at maximum load. When regression was done between pilodyn penetration depth and specific gravity in each of the species, it was noticed that a linear relationship existed between them. A linear relationship was found to exist between dynamic MOE and static MOE among the species. It can be concluded from the study that both pilodyn and treesonic timer can be used as predictors of timber properties under field conditions.